Tahap Penguasaan Sorof Di Kalangan Pelajar-Pelajar Kolej Universiti Islam Malaysia (KUIM) - Rosni Samah; Arnida A. Bakar (Universiti Sains Islam Malaysia, 2024)
Morphology is part of the main subjects in Arabic language learned by the students in order to know the Arabic root word and its meaning. Most of the students at religious schools have learned this subject since they are in form one. The learning process of this subject is continuing until they are in form five and six. Students at the Islamic University College of Malaysia (KUIM) have learned this subject at their former schools as well. The aim of this research is to identify the level of acquisition among Islamic University College of Malaysia (KUIM) students in mastering this subject. Three different aspects have been identified which are: first, the ability of the students in recognizing various forms of words. Secondly, the questionnaire also tried to test their knowledge skills in identifying the root word. Moreover, it examined their awareness of the changes of the words according to certain forms that have been made to suit the meaning intended in the text. Lastly, their competency in knowing the meaning of the words according to its form was also tested. About 21 1 questionnaires were distributed to the first year and second year students. It was found that they were lack of knowledge in those three aspects. This has been proven via the result obtained from the survey. Several solutions have been suggested as to improve their level of competency in this subject and for the betterment of the teaching of Arabic language especially in this university.